2010
DOI: 10.1074/jbc.m109.099424
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Chemokine Receptor CCR1 Causes Osteopenia Due to Impaired Functions of Osteoclasts and Osteoblasts

Abstract: Chemokines are characterized by the homing activity of leukocytes to targeted inflammation sites. Recent research indicates that chemokines play more divergent roles in various phases of pathogenesis as well as immune reactions. The chemokine receptor, CCR1, and its ligands are thought to be involved in inflammatory bone destruction, but their physiological roles in the bone metabolism in vivo have not yet been elucidated. In the present study, we investigated the roles of CCR1 in bone metabolism using CCR1-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 45 publications
(40 reference statements)
10
74
1
Order By: Relevance
“…Future studies will elucidate whether autocrine EBI2 signaling is constitutive or inducible in OCPs and whether it is altered during pathological conditions. Although EBI2 contributes and is sufficient to promote OCP movement and differentiation in vivo, EBI2-deficient Hoshino et al, 2010). Our study revealed that autocrine EBI2 signaling accelerated OCP movement in vitro, which presumably maximized cell-cell interactions that precede cell fusion.…”
Section: Discussionmentioning
confidence: 81%
“…Future studies will elucidate whether autocrine EBI2 signaling is constitutive or inducible in OCPs and whether it is altered during pathological conditions. Although EBI2 contributes and is sufficient to promote OCP movement and differentiation in vivo, EBI2-deficient Hoshino et al, 2010). Our study revealed that autocrine EBI2 signaling accelerated OCP movement in vitro, which presumably maximized cell-cell interactions that precede cell fusion.…”
Section: Discussionmentioning
confidence: 81%
“…2E), since we had previously reported critical roles of the CCR1 axis involving CCL5 and CCL9 in the differentiation and function of both osteoblasts and osteoclasts by observing Ccr1-deficient mice (Hoshino et al, 2010). Interestingly, the expression of Cx3cl1, Ccr1 and Ccl9 was almost completely eliminated, and CX3CR1-CX3CL1 axis in bone metabolism 1033 the level of Ccl5 was significantly downregulated in the bones from Cx3cr1-deficient mice (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Bone cells derived from Ccr1 2/2 mice show diminished expression levels of several chemokine ligands, thus suggesting that hierarchal networks of chemokines participate in bone metabolism (Hoshino et al, 2010). Therefore, in the present study, we investigated the bone features of Cx3cr1-deficient mice to further assess the roles of the chemokine receptors in bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The profile of chemokine receptors was analyzed by flow cytometry of human MSCs, and the results revealed that at least 70% of MSCs express CCR1, while none express CCR3 or CCR5 (9). Moreover, modulating the receptor activator of nuclear factor-κB ligand (RANKL)/RANK mediated interaction and osteoclast/osteoblast function in a mouse model (10), and osteopenia occur within CCR1-deficienct mice where they have fewer and thinner trabecular bones.…”
Section: Introductionmentioning
confidence: 99%